MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS DAN KEAKTIFAN PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA PADA MATERI PERSAMAAN GARIS SINGGUNG ELIPS SISWA KELAS XII SMA NEGERI 11 SEMARANG TAHUN PELAJARAN 2024/2025 - Jami'atun, Siti; Sulistiyoningsih, Titien; Prihaswati, Martyana (Journal of Lesson Study in Teacher Education, 2025)
One of the mathematical skills that students must master is the ability to reason mathematically. However, in reality, this skill has not yet been fully mastered by students. This study is a classroom action research conducted over two cycles at SMA Negeri 11 Semarang. The subjects of the study were students from class XII D-1. The purpose of this study are to describe the process of implementing mathematics learning through the Problem Based Learning (PBL) model assisted by GeoGebra as an effort to improve students' mathematical reasoning abilities and learning engagement in class XII D-1 on the topic of ellipses at SMA Negeri 11 Semarang, to determine the improvement in students' mathematical problem-solving abilities in class XII D-1 on the topic of ellipses after mathematics learning through the Problem Based Learning model assisted by GeoGebra, and to determine the improvement in students' learning engagement in class XII D-1 on the topic of ellipses at SMA Negeri 11 Semarang after the implementation of mathematics learning through the Problem Based Learning model assisted by GeoGebra. The results of the study indicate an improvement in students' mathematical reasoning abilities and learning engagement